In vitro activity effects of combinations of cephalothin, dicloxacillin, imipenem, vancomycin and amikacin against methicillin-resistant Staphylococcus spp. strains - Solórzano-Santos Fortino; Vilchis-Pérez Mariano; Leaños-Miranda Blanca E; Miranda-Novales Guadalupe (BMC, 2006)
Abstract Background combinations of drugs has been proposed as an alternative for oxacillin-resistant staphylococci infections, however, limited information about in vitro combinations are available for multi-resistant strains. The objective of this study was to describe the interaction of beta-lactams in combination with vancomycin or amikacin against 26 oxacillin and amikacin-resistant nosocomial Staphylococcus spp. isolates. Methods activity of dicloxacillin plus amikacin, cephalothin plus amikacin, cephalothin plus vancomycin, imipenem plus vancomycin and vancomycin plus amikacin was evaluated by checkerboard synergy tests and the fractional inhibitory concentration index (FIC) was calculated. Results: dicloxacillin plus amikacin, and cephalothin plus amikacin were synergistic or partially synergistic in 84.6% and 100% respectively. For nearly half of the isolates the mean concentrations of dicloxacillin, cephalothin and amikacin at which FIC indexes were calculated were achievable therapeutically. Vancomycin plus amikacin had synergistic effect only against two isolates, and partially synergistic in 38.6%. For the combinations vancomycin plus cephalothin and vancomycin plus imipenem the effect was additive in 76.9% and 80.7% respectively. Conclusion in this study the checkerboard analysis showed that amikacin in combination with cephalothin or dicloxacillin was synergistic against most of the resistant strains of S. aureus and coagulase-negative Staphylococcus. Vancomycin in combination with a beta-lactam (cephalothin or imipenem) showed additivity. An indifferent effect predominated for the combination vancomycin plus amikacin. Even though a synergistic effect is expected when using a beta-lactam plus amikacin combination, it is possible that the effect cannot be clinically achievable. Careful selection of antimicrobial combinations and initial MICs are mandatory for future evaluations.